Historical narrative as a form of organization and representation of historical knowledge - Mishalova, Olena (Actual Problems of Mind, 2017)
The paper presents the main principles of a narrative philosophy of history which substantiates radically new understanding of a historical text (narrative). The author proposes to consider historical narrative as a form of organization and representation of historical knowledge analogous to theory in the natural and exact sciences, in accordance with specific standards of scientific rigor in history and humanities as such.